A structural equation model of online learning: investigating self-efficacy, informal digital learning, self-regulated learning, and course satisfaction - Zheng, Yi; Xiao, Ao (Frontiers in Psychology, 2024)
In the context of English as a Foreign Language (EFL) education, where online learning plays a pivotal role, comprehending the intricate interplay between critical factors is not just essential but also holds profound significance for enhancing learning experiences. This research goes beyond the surface to explore the complex web of relationships between online learning selfefficacy, online self-regulated learning, Informal Digital Learning of English (IDLE), and online course satisfaction, specifically tailored to the unique needs and challenges of EFL learners. The study encompassed 563 intermediate college students from multiple national universities in China. The results from Structural Equation Modeling (SEM) demonstrated compelling insights.Firstly, both online learning self-efficacy and IDLE showed direct and positive effects on online course satisfaction. Additionally, the study revealed that online self-regulated learning served as a partial mediator in the relationship between online learning self-efficacy and IDLE with online course satisfaction. This mediation effect suggests that learners' self-regulatory behaviors play a pivotal role in influencing the impact of self-efficacy and informal digital language learning experiences on their overall satisfaction with online courses. The findings underscore the importance of nurturing learners' self-efficacy beliefs, fostering IDLE, and promoting effective self-regulated learning strategies in the context of online language learning. Such initiatives can significantly contribute to enhancing learners' satisfaction and success in online courses. The implications of these findings for EFL instruction are finally elaborated on.